Intertextuality in The Two Noble Kinsmen - Andrejević, Ana M.; Zečević, Snežana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The central plot of Fletcher and Shakespeare’s play The Two Noble Kinsmen derives from Chaucer’s The Knight’s Tale, so it could be interpreted through the theory of intertextuality and transtextuality. The prototext of these literary works is identical, but it has been modified over the centuries. It has changed from a mythological story into a universal symbol of love, friendship, authority, honor, and death. Apart from the permutation of texts by different authors, The Two Noble Kinsmen is also a curious collection of Shakespeare’s earlier works, despite the frequent contestation of his contribution to this play. Such self-citation is an interesting phenomenon, especially if we consider the fact that this play is Shakespeare’s last work and not The Tempest, as traditionally stated in literary histories. Therefore, this paper aims to determine the similarities and differences between Chaucer’s famous story and Fletcher and Shakespeare’s play, to point out the degree of intertextuality in it, and to highlight the original dramatic episodes and characters, their function, meaning, and significance. With the assumption that Fletcher and Shakespeare intentionally and purposefully chose the mode of adaptation and transformation of the famous Chaucer’s text, the obtained results indicate that certain elements were modified due to the requirements of the dramatic form and its theatrical function, but also for commercial and socio-political reasons. The transposition of the well-known ancient story into Renaissance England, with new episodes and characters in the subplot, offers a different and somewhat subversive picture of conventional social norms and relations.